STIMULASI MOTIVASI INTRINSIK DAN FLOW STATE ANAK MELALUI PEMBELAJARAN DEEP LEARNING BERBASIS VISUAL MAKRO - Tsabita Tasya, Farah; Sholikhin, Anwar; Winnuly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the prevalence of learning apathy in early childhood due to conventional learning patterns that are mechanistic and superficial, thereby reducing students' cognitive engagement. The purpose of this study is to analyze the teacher's strategy in planning and implementing Deep Learning based on Canva-integrated macro visuals, as well as to identify supporting and inhibiting factors in stimulating children's intrinsic motivation and total concentration state (flow state). The research method used is descriptive qualitative with a case study design at RA I’anatut Tholibin Lamongan, with research subjects including classroom teachers and 18 students. Data collection techniques were carried out through data triangulation including participant observation, in-depth interviews, and systematic documentation analysis. The results showed that in the planning stage, the teacher successfully optimized the Canva platform to produce A3-sized spiral-bound macro visual media that is friendly to children's working memory capacity. In the implementation stage, the teacher transformed into a cognitive facilitator by applying interactive literacy techniques through open-ended questions based on